Pengaruh Pendidikan Terhadap Kinerja Karyawan di Moderasi Keterlibatan Karyawan - Rikardus Outniel Yunatan; Vincent Gaspersz; Henny A. Manafe (Univiversitas Dr. Djar Wattiheluw, 2023)
This study aims to analyze the role of work involvement moderation from the direct relationship between education and employeeperformance in CV MSMEs. C & A in Kupang City. The population in this study was 64 employees which were then used as samples with census/saturated techniques. Data analysis techniques using moderation analysis with the help of SmartPLS version 3.30. The results showed that education directly has a positive and significant effect on employee performance, but work involvement does not moderate the relationship between education and employee performance.